Sensory Characteristics of Cow's Milk Yogurt with the Addition of Kecombrang Stem Extract - Nurhopipah, Popi; Naufalin, Rifda; Wicaksono, Rumpoko (Indonesian Journal of Food Technology, 2024)
Yogurt is a fermented dairy product that plays an important role in the balance of microflora in the human digestive system. The functional properties of yogurt can be enhanced by adding bioactive components from kecombrang (Etlingera elatior) extract. Kecombrang is a spice plant belonging to the Zingiberaceae family and has been used in food products. The commonly used parts of this plant are the flowers, leaves, and stems. The purpose of this research is to determine the sensory characteristics of cow's milk yogurt with the addition of kecombrang stem extract. The experimental design used was a Completely Randomized Design (CRD) with the factor being the concentration of kecombrang stem extract added, which was 2.5%, 5%, and 7.5%. Data analysis used Analysis of Variance (ANOVA) at a significance level of 5%. The results of the study showed that the addition of kecombrang stem extract did not have a significant effect (p>0.05) on the sensory characteristics of yogurt.